2021
DOI: 10.1127/fal/2020/1315
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes in the macroinvertebrate community in Alpine stream networks fed by shrinking glaciers

Abstract: The status of glaciers is alarming globally with still unknown effects on freshwater ecosystems. Thegeneral aim of this study was to investigate the structural and functional changes in the macroinvertebrate communityin stream networks fed by shrinking glaciers in relation to environmental variables. Feeding glaciers haddifferent surface areas and retreating rates. We selected 10 study sites in the Italian Alps, spanning five kryal, twoglacio-rhithral, two krenal and one proglacial pond, sampled twice in summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Within this scenario, Diamesa species are seriously threatened by extinction in concomitance with the disappearance of the kryal habitat, leading to the decrease of regional biodiversity (Jacobsen et al., 2012). Among the Diamesa species most sensitive to climate change and hypothesized to disappear in the Alps ( D. steinboecki , D. goetghebueri, and D. zernyi ) (Lencioni, 2018), the “glacier fly” D. steinboecki (Serra‐Tosio, 1974) is the species most likely to disappear first (Lencioni et al., 2021). These findings make D. steinboecki the best indicator of high glacial level in the Southern Alps: the “flagship” species of the Alpine kryal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this scenario, Diamesa species are seriously threatened by extinction in concomitance with the disappearance of the kryal habitat, leading to the decrease of regional biodiversity (Jacobsen et al., 2012). Among the Diamesa species most sensitive to climate change and hypothesized to disappear in the Alps ( D. steinboecki , D. goetghebueri, and D. zernyi ) (Lencioni, 2018), the “glacier fly” D. steinboecki (Serra‐Tosio, 1974) is the species most likely to disappear first (Lencioni et al., 2021). These findings make D. steinboecki the best indicator of high glacial level in the Southern Alps: the “flagship” species of the Alpine kryal.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for its disappearance are yet to be fully understood. It was suggested that its strong cold stenothermy and cold hardiness could prevent it from adapting to water only 2–4 degrees warmer than its thermal optimum (2°C) (Lencioni et al., 2021). Also, competition for food and space with newly colonizing species and predator range shifts can negatively impact on D. steinboecki (Khamis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions to this Special Issue highlight the vibrancy of research activity within freshwater sciences across and beyond Europe. Much of the research presented focuses on freshwaters of conservation interest, from those within protected national parks (Buj et al 2020;Ivić et al 2020;Vurnek et al 2020) to those in vulnerable areas of the Alpine region (Carosi et al 2020;Lencioni et al 2020). As European freshwaters continue to respond to climate change and other anthropogenic pressures, such research will underpin effective monitoring and management strategies that support biodiversity within functional ecosystems (Markovic et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notable changes in community composition over the 22-year study period reflected the loss of strict kryal species such as the chironomid Diamesa steinboecki (Diptera: Chironomidae) and upstream migration of generalist insects, with consequent changes in food web structure. Lencioni et al (2020) thus suggest D. steinboecki as a 'flagship' species of kryal Alpine streams: a species that may be lost as sites pass 'tipping points' in response to rapid global warming.…”
Section: Structural and Functional Responses To Disturbancementioning
confidence: 99%
See 1 more Smart Citation